2005
DOI: 10.1097/01.alc.0000150009.78622.e0
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Accumbal Glycine Receptors in the Regulation of Voluntary Ethanol Intake in the Rat

Abstract: The present findings suggest that glycine and strychnine alter extracellular DA levels in the nAc, probably via GlyR stimulation and blockade, respectively, and concomitantly glycine and strychnine reciprocally alter also EtOH consumption in EtOH high-preferring male Wistar rats. The possibility of developing selective GlyR agonists and/or antagonists should be explored. Such agents could prove of value in the treatment of alcoholism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
106
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(114 citation statements)
references
References 46 publications
7
106
1
Order By: Relevance
“…It warrants further investigation. Our finding is in general agreement with a previous study that showed that intra-NAc glycine induced an increase in DA levels in the NAc and was associated with a reduced ethanol consumption in a subgroup of Wistar rats (Molander et al, 2005). It is possible that elevated DA levels in the NAc would produce reward, and therefore the animals would not need to drink as much ethanol in order to achieve the desired effect, thereby resulting in decreased ethanol intake and preference.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It warrants further investigation. Our finding is in general agreement with a previous study that showed that intra-NAc glycine induced an increase in DA levels in the NAc and was associated with a reduced ethanol consumption in a subgroup of Wistar rats (Molander et al, 2005). It is possible that elevated DA levels in the NAc would produce reward, and therefore the animals would not need to drink as much ethanol in order to achieve the desired effect, thereby resulting in decreased ethanol intake and preference.…”
Section: Discussionsupporting
confidence: 93%
“…The DA system is under the control of several neurotransmitter systems, including the GABA A receptors and GlyRs (Ye et al, 2001;Molander et al, 2005). A previous microdialysis study has demonstrated that GlyRs in the NAc are involved in both the regulation of basic dopamine levels and NAc dopamine output in response to ethanol (Molander et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In relevance to alcohol abuse, it is now accepted that GlyRs are a major target for the intoxicating effects of ethanol as suggested by previous studies from our and other groups (Aguayo et al, 1996;Findlay et al, 2002;Molander et al, 2005Molander et al, , 2007. Therefore, the present results are relevant because we show that a small heptadecapeptide can antagonize the alcohol effect on an LGIC, opening new possibilities for the study of small organic molecules that can interfere with the intoxicating effect of ethanol, which supports previous work in relation to the development of compounds that can affect G protein activity (Davis et al, 2005;Bonacci et al, 2006).…”
Section: Discussionmentioning
confidence: 70%
“…For example, bilateral infusions of glycine into the nucleus accumbens increase dopamine release and reduce ethanol drinking and preference, and injections of glycine reuptake inhibitors reduce ethanol intake and preference (Molander et al, 2005(Molander et al, , 2007Lido et al, 2011). Reduction in alcohol intake by injection of glycine appears contradictory to our results, showing that mutations that reduce alcohol potentiation of GlyR function also reduce drinking .…”
Section: Zinc and Ethanol Modulation Of Glycine Receptor Functionmentioning
confidence: 99%